NON-INVASIVE METHODS FOR TREATING DIABETES INSIPIDUS - Salimova , Dildora Erkinovna; Sitora, Ilhomjonova; Olimova, Aziza; Askarova , Jasmina (Educational Research in Universal Sciences, 2024)
Endocrinology is a branch of medicine that studies the endocrine system and its functions, as well as diseases associated with disruption of the endocrine glands. In this article, we will look at the basic concepts and principles of endocrinology, as well as some common endocrine diseases. To diagnose and treat endocrine diseases, an endocrinologist may use a variety of techniques, including blood tests to determine hormone levels, imaging (such as ultrasound or MRI) to study the structure of the endocrine glands, and specialized tests and procedures.